Measurement of the Sensitivity for Diving-bell Manometer - Culma Caviedes, Jose Eduin; Culma Caviedes, Jose Eduin (IMEKO International Measurement Confederation, 2018)
Diving-bell manometers are devices mainly used for low-gauge measurements, with a variety of industrial and medical applications. At the Colombian Instituto Nacional de Metrología, a Junkalor Dessau TMG 25/1104 diving-bell manometer was subjected to sensitivity verification, with 200 mg as the discrimination threshold. Considering that this manometer works analogously to an equal arm balance, sensitivity is defined as the weight change on the balance that is needed to produce a movement larger that the smallest estimable fraction of a scale interval determined by visual interpolation component (resolution on the indicator element). Three set data points were evaluated: the first, with 20 g placed on each plate; the second, with 19.7 g on the left plate and 20 g placed on the right plate; and the third, with 20.3 g on the left plate and 20 g on the right plate. Recommendations for use of the diving bell are made and the resolution for the device was determined.